Longitudinal Mediators of Relations Between Family Violence and Adolescent Dating Aggression Perpetration. Issue 4 (21st April 2015) - Reyes, H. Luz McNaughton; Foshee, Vangie A.; Fortson, Beverly L.; Valle, Linda A.; Breiding, Matthew J.; Merrick, Melissa T.
<x xml:space="preserve">Abstract</x> Few longitudinal studies have examined the pathways through which family violence leads to dating aggression. In the current study the authors used 3 waves of data obtained from 8th‐ and 9th‐grade adolescents (N = 1, 965) to examine the hypotheses that the prospective relationship between witnessing family violence and directly experiencing violence and physical dating aggression perpetration is mediated by 3 constructs: (a) normative beliefs about dating aggression (norms), (b) anger dysregulation, and (c) depression. Results from cross‐lagged regression models suggest that the relationship between having been hit by an adult and dating aggression is mediated by changes in norms and anger dysregulation, but not depression. No evidence of indirect effects from witnessing family violence to dating aggression was found through any of the proposed mediators. Taken together, the findings suggest that anger dysregulation and normative beliefs are potential targets for dating abuse prevention efforts aimed at youth who have directly experienced violence.